Understanding the complex function of gut microbiota: its impact on the pathogenesis of obesity and beyond: a comprehensive review - Aref Yarahmadi; Hamed Afkhami; Ali Javadi; Mojtaba Kashfi (Diabetology & Metabolic Syndrome)
Abstract Obesity is a multifactorial condition influenced by genetic, environmental, and microbiome-related factors. The gut microbiome plays a vital role in maintaining intestinal health, increasing mucus creation, helping the intestinal epithelium mend, and regulating short-chain fatty acid (SCFA) production. These tasks are vital for managing metabolism and maintaining energy balance. Dysbiosis—an imbalance in the microbiome—leads to increased appetite and the rise of metabolic disorders, both fuel obesity and its issues. Furthermore, childhood obesity connects with unique shifts in gut microbiota makeup. For instance, there is a surge in pro-inflammatory bacteria compared to children who are not obese. Considering the intricate nature and variety of the gut microbiota, additional investigations are necessary to clarify its exact involvement in the beginnings and advancement of obesity and related metabolic dilemmas. Currently, therapeutic methods like probiotics, prebiotics, synbiotics, fecal microbiota transplantation (FMT), dietary interventions like Mediterranean and ketogenic diets, and physical activity show potential in adjusting the gut microbiome to fight obesity and aid weight loss. Furthermore, the review underscores the integration of microbial metabolites with pharmacological agents such as orlistat and semaglutide in restoring microbial homeostasis. However, more clinical tests are essential to refine the doses, frequency, and lasting effectiveness of these treatments. This narrative overview compiles the existing knowledge on the multifaceted role of gut microbiota in obesity and much more, showcasing possible treatment strategies for addressing these health challenges.